2021
DOI: 10.1038/s41390-021-01529-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle function in the newborn: a narrative review

Abstract: Our aim was to summarise the current evidence and methods used to assess respiratory muscle function in the newborn, focusing on current and future potential clinical applications. The respiratory muscles undertake the work of breathing and consist mainly of the diaphragm, which in the newborn is prone to dysfunction due to lower muscle mass, flattened shape and decreased content of fatigue-resistant muscle fibres. Premature infants are prone to diaphragmatic dysfunction due to limited reserves and limited cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 115 publications
1
31
2
1
Order By: Relevance
“…Some previous studies have reported a higher PMA to be predictive of extubation failure, 8 with the authors suggesting that it is the prolonged period of ventilation prior to extubation that causes disuse atrophy of the diaphragm and thus subsequent extubation failure. 7 , 45 Within our study, there was no difference, however, in the duration of invasive mechanical ventilation prior to extubation between those who were successfully extubated and those infants who were not. Indeed, our finding that a higher PMA is associated with successful extubation has been demonstrated in other previous studies and may also be linked to such infants having greater brain maturity, the development of which is crucial in controlling and regulating breathing.…”
Section: Discussioncontrasting
confidence: 44%
“…Some previous studies have reported a higher PMA to be predictive of extubation failure, 8 with the authors suggesting that it is the prolonged period of ventilation prior to extubation that causes disuse atrophy of the diaphragm and thus subsequent extubation failure. 7 , 45 Within our study, there was no difference, however, in the duration of invasive mechanical ventilation prior to extubation between those who were successfully extubated and those infants who were not. Indeed, our finding that a higher PMA is associated with successful extubation has been demonstrated in other previous studies and may also be linked to such infants having greater brain maturity, the development of which is crucial in controlling and regulating breathing.…”
Section: Discussioncontrasting
confidence: 44%
“…From this perspective, US measurements will rather supplement than replace pulmonary function assessment. At present, US measurements are useful (i) in assessing diaphragm dysfunction (paralysis [37], asymmetrical movements [55], congenital anomalies [56]) or (ii) as a prognostic marker for frequent exacerbations in COPD patients [32]. It is also worth considering US measurements of the diaphragm in surgical management/repair of congenital diaphragmatic hernia [57][58][59] and as an additional indicator in the assessment of effort tolerance in pulmonary rehabilitation or rehabilitation progress [60].…”
Section: Clinical Contextmentioning
confidence: 99%
“…Loss of muscle function can lead to many diseases, including stroke, spinal cord injury, and multiple sclerosis [ 75 , 76 ]. Electrical stimulation has positive effects when treating this disease.…”
Section: Long-term Self-treatment Equipmentmentioning
confidence: 99%